2020
DOI: 10.3164/jcbn.19-65
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of salt intake from spot urine may assist the risk assessment of gastric cancer

Abstract: Daily salt intake can be estimated by measuring sodium and creatinine concentrations in spot urine. Excessive salt intake is risk factor for gastric cancer. We examined the correlation between estimated salt intake from spot urine and risk of gastric cancer. This study included gastric cancer patients who underwent treatment at our hospital and patients in whom esophagogastro duodenoscopy was performed but gastric cancer was not observed. The history of H. pylori infection was known in these patients. Spot uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Gastric cancer remains a major threat to human health. Excessive intake of salt/salty foods, as well as insufficient intake of fresh fruits and vegetables, can increase the risk of gastric cancer [ 26 ]. It is well-documented that daily eating habits are closely associated with the occurrence of gastric diseases, including gastric cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer remains a major threat to human health. Excessive intake of salt/salty foods, as well as insufficient intake of fresh fruits and vegetables, can increase the risk of gastric cancer [ 26 ]. It is well-documented that daily eating habits are closely associated with the occurrence of gastric diseases, including gastric cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium ions (Na + ) play vital physiological roles such as maintenance of body osmolality, nerve and muscle cell excitation, and absorption of nutrients in the gastrointestinal tract.‍ ( 1 ) However, excessive salt intake leads to elevated blood pressure, thus increasing the risk of cerebrocardiovascular events and kidney disease,‍ ( 2 ) and is implicated in a variety of other conditions such as gastric cancer, asthma, and osteoporosis.‍ ( 3 5 ) A technical report by the World Health Organization (WHO) and the Food and Agriculture Organization of the United Nations has recommended a salt consumption level of less than 5 g per day as a nutrient intake goal. In Japan, the number of patients with metabolic syndrome and diabetes mellitus has increased with the westernization of dietary habits.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is firmly associated with Helicobacter pylori ( H. pylori ).‍ ( 1 ) A prospective, long-term study showed that there were no cases of gastric cancer in H. pylori un-infected group.‍ ( 2 ) However, in clinical practice, we occasionally encounter a small number of gastric cancers in H. pylori un-infected cases.‍ ( 3 ) Besides H. pylori , there are other carcinogenic factors for gastric cancer such as Epstein–Barr virus infection, high salt intake, genetic factors and so on.‍ ( 4 6 )…”
Section: Introductionmentioning
confidence: 99%
“…(3) Besides H. pylori, there are other carcinogenic factors for gastric cancer such as Epstein-Barr virus infection, high salt intake, genetic factors and so on. (4)(5)(6) The prevalence of H. pylori has decreased during several decades due to improvements in the sanitary environment and widespread eradication of H. pylori in Japan. (7,8) Therefore, a relative increase is expected in the incidence of H. pyloriuninfected gastric cancer.…”
mentioning
confidence: 99%